Дядя Степа - Михалков Сергей Владимирович (Все для детского сада, 2017)
Экземпляры: ф.2 (20180208) / Инвентарный номер: 54734 / Цена: 80.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 69 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6